UPAYA GURU DALAM MEMBENTUK KEMANDIRIAN BELAJAR SISWA KELAS V SEKOLAH DASAR - Firdaus, Husni; Asy’ari, Lutfi; Nugraha, Widdy Sukma (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
This study aims to determine student learning independence and to find out the efforts made by teachers in establishing learning independence for fifth grade students at SDN 4 Karangsari Cikelet, Garut Regency. The method used in this research is a qualitative approach. The methods are Observation, Interview and Documentation. The results showed that: 1) Planning, the teacher has described all the plans in the syllabus and lesson plans. The preparation of the Learning Implementation Plan (RPP) made by the teacher is developed in the syllabus. 2) Implementation, the teacher's role in shaping student learning independence can be seen from the media used, namely the appearance of videos and pictures using power point, as well as using the methods of discussion, question and answer, problem solving, socio drama and assignments. 3) Evaluation in the learning process to obtain information on the achievement of learning objectives which is carried out continuously